Perspectives of Veterinary Science - John A. L. Maxwell (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
The veterinary art has been practiced for the last 4,000 years as a trade. The first record of this trade is found in the Hammurabi Code of Law, established 2,000 years before the birth of Jesus Christ. Two hundred and fifty (250) years ago, an effort was made to change the trade into a science. Claude Bourgelat, a French veterinary surgeon, established a School for Veterinary Science at Lyon in France in 1761. Since then, the profession of Veterinary Science has become established throughout the world. In Australia, the first school opened in 1888, with the establishment of a private veterinary school, in conjunction with a practice in Melbourne. Has this revolution been a success; has it led to more competent, better educated and trained veterinary graduates? John Maxwell, has devoted the last phase of his life in the profession of veterinary science examining this question. In research conducted during the first 20 years of this century, he has examined this issue in detail, leading to the awarding of not one, but two doctorates. Surveys of the profession and oral history interviews of individuals intimately involved in various aspects of veterinary science have been conducted, leading to the awarding of a PhD in 2008 and a DVMSc in 2018. Contrary to expectations the result has been a resounding, No! The experiment with science has been a failure. As a result, Dr Maxwell was led to examine the past to discover if there could be a future for individuals wishing to work in animal health.